2020
DOI: 10.1016/j.amsu.2020.07.030
|View full text |Cite
|
Sign up to set email alerts
|

A sharp increase in the number of COVID-19 cases and case fatality rates after lifting the lockdown in Kurdistan region of Iraq

Abstract: With the appearance of first cases of Coronavirus disease (COVID-19), strict control measures were implemented in the Kurdistan Region of Iraq to combat the infection. These measures included the closure of schools and universities, the closure of borders and airports, cancellation of public and religious gatherings, and mandatory quarantine for persons returning from traveling abroad. Such measures have played a major role in the control of COVID-19 spread. However, due to social and economic pressures, the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 3 publications
2
33
1
Order By: Relevance
“…In the current report, we presented the first case of COVID-19 reinfection in Iraq. Similar to the case report in the United States, the second infection was associated with increased symptoms, which required antiviral treatment (5). This is in contrast to the case reports in Hong Kong, Belgium, and Netherlands, in which the severity of the cases has been reported to be the same in both rounds of the infection (3,4).…”
Section: Discussionsupporting
confidence: 79%
“…In the current report, we presented the first case of COVID-19 reinfection in Iraq. Similar to the case report in the United States, the second infection was associated with increased symptoms, which required antiviral treatment (5). This is in contrast to the case reports in Hong Kong, Belgium, and Netherlands, in which the severity of the cases has been reported to be the same in both rounds of the infection (3,4).…”
Section: Discussionsupporting
confidence: 79%
“…[ 6 ] Such measures included the shutdown of cities, closure of educational institutions, shopping mall, workplaces, and roads. [ 5 ] In addition, the present study found that higher knowledge score about the infection was significantly associated with a higher likelihood of positive attitude and good practice during the period of COVID-19 outbreak. The practices of university students toward the virus were extremely cautious as the majority of the recruited sample (93%) avoided crowded places and more than a half of participants (57.3%) wore masks when going out the home during the period of the outbreak.…”
Section: Discussionmentioning
confidence: 51%
“…These measures include the suspension of public transport; the closure of educational institutions; the prevention of public gatherings and events such as daily and Friday prayers, Church gathering, weddings, and funerals; the isolation of infected people; and the quarantine of suspected cases. [ 5 ] Since March 15, 2020, the Kurdistan authorities have locked down the region, and people were required to stay home. [ 6 ] Community health prevention program cannot be successful without health education programs which increase the commitment to control measures.…”
Section: Introductionmentioning
confidence: 99%
“…The government’s actions in this regard were then limited to the giving of instructions, and those who did not follow the instructions were not penalized. The number of COVID-19 cases increased sharply until November 2020, when a sharp decrease in the number of cases was observed [3,4]. Our study shows that the number of cases decreased significantly in the following months.…”
Section: Discussionmentioning
confidence: 64%
“…The implementation of these measures began on March 1, 2020, and continued until May 21, 2020. After the measured were relaxed, a sharp increase in morbidity and mortality was recorded [3,4]. Despite this, there was an unwillingness in society to follow the social-distancing instructions [5].…”
Section: Introductionmentioning
confidence: 99%